Verb Structure and Grammatical Encoding in the Spontaneous Speech of Indonesian Speakers with Broca’s Aphasia - Harwintha Yuhria Anjarningsih; Kharisma Ulinnuha; Myrna Laksman-Huntley (Badan Pengembangan dan Pembinaan Bahasa, 2023)
This study aimed to obtain the characteristics of verb structure in the speech of Indonesian speakers with Broca’s aphasia and their relation to the Argument Structure Complexity Hypothesis (ASCH) and grammatical encoding. There are three questions, namely the interrelationships of verbs and syntactic functions, interrelationship of verbs and semantic functions, and the contribution to the ASCH and grammatical coding. Eight participants took part, divided into four with aphasia and four Non-Brain Damaged (NBD) participants as controls. The research used an experimental research method. The instruments were five images adapting Cookie Theft (an instrument used in an aphasia test in various languages) and 3 instructions to tell about daily activities. The results showed that participants with aphasia tended to use verbs in simpler structures than controls. Therefore, this study supports the ASCH about the argument simplification and tendency of grammatical coding problems, important as coming from Indonesian, an Austronesian language. Clinical implications are discussed. AbstrakPenelitian ini bertujuan untuk mendapatkan karakteristik struktur verba dalam tuturan spontan penutur Bahasa Indonesia dengan afasia Broca dan hubungannya dengan Argument Structure Complexity Hypothesis (ASCH) dan pengkodean gramatikal. Ada tiga pertanyaan penelitian, yaitu keterkaitan verba dan fungsi sintaksis, keterkaitan verba dan fungsi semantik, dan kontribusi terhadap ASCH dan pengkodean gramatikal. Delapan peserta ikut serta, dibagi menjadi empat dengan afasia dan empat peserta tanpa gangguan syaraf (Non-Brain Damaged: NBD) sebagai kontrol. Metode penelitian yang digunakan adalah metode eksperimental. Instrumen yang digunakan adalah lima buah gambar yang mengadaptasi Cookie Theft (instrumen dalam tes afasia lintas bahasa) serta tiga buah instruksi untuk bercerita tentang kegiatan sehari-hari. Hasil penelitian menunjukkan bahwa peserta dengan afasia cenderung menggunakan verba dalam struktur yang lebih sederhana daripada peserta NBD. Oleh karena itu, penelitian ini mendukung ASCH tentang penyederhanaan argumen dan kecenderungan terjadinya masalah pengkodean gramatikal. Dukungan ini penting karena datang dari Bahasa Indonesia yang merupakan bahasa rumpun Austronesia. Implikasi klinis juga disarankan.